1990
DOI: 10.1159/000284650
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Suicidal Crises: Characteristics of Repeating versus Nonrepeating Suicidal Visitors to a Psychiatric Emergency Service

Abstract: The present study involves a retrospective chart review of all patients who visited the Emergency Mental Health Service during the period of July, 1, 1985 to June, 30, 1986 (total visits = 2,772). It compares those ‘suicidal’ patients seen only once during the index year with those seen multiple times (comparison of first visit only for both ‘one-timers’ and ‘repeaters’). The ‘repeaters’ were generally found to be older and were more likely to have a diagnosis of schizophrenia and personality disorder. Unlike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Individuals who presented in suicidal crisis on more than one occasion were classified a ‘repeating-patients’. Based on Peterson and Bongar’s 10 definition of chronicity, individuals who had four or more presentations were defined as ‘chronic repeating-patients’.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals who presented in suicidal crisis on more than one occasion were classified a ‘repeating-patients’. Based on Peterson and Bongar’s 10 definition of chronicity, individuals who had four or more presentations were defined as ‘chronic repeating-patients’.…”
Section: Methodsmentioning
confidence: 99%
“…Critical to this decision is the discrimination of the relative contributions of acute clinical states and more pervasive personality characteristics (Bongar, 1991;Goldsmith, Fyer, & Frances, 1990). Research relative to personality functioning in suicidal samples indicates significantly increased incidence of personality disorder diagnoses among both suicide attempters and ideators (Barraclough, Bush, Nelson, & Sainsbury, 1974;Cantor, 1976;Hawton, 1987;Lall, 1994;Peterson & Bongar, 1990;Schuckit & Gunderson, 1974;Seager, 1986;Wade, 1987). Additionally, behaviors characteristic of personality pathology (e.g., interpersonal conflict, self-destructive behavior, attention-seeking, etc.)…”
Section: Personality and Suicide Riskmentioning
confidence: 99%
“…Research on parasuicide has shown that a number of variables discriminate between repeaters and nonrepeaters when they are compared retrospectively. Compared to nonrepeaters, repeaters more often suffer from some kind of psychiatric disorder, have received psychiatric treatment or been in contact with some health service, abuse alcohol andlor drugs, live alone, are unemployed or economically inactive, and have experienced suicidal behavior in their family (Bagley, 1970;Bagley & Greer, 1971;Barnes, 1986;Buglass & Horton, 1974a;Gupta et al, 1992;Kotila & Lonnqvist, 1987;Krarup, Nielsen, Rask, & Petersen, 1991;Kreitman & Casey, 1988;Kreitman & Foster, 1991;Morton, 1993;Ojehagen, Regn611, & Traskman-Bendz, 1991;Peterson & Bongar, 1990;Petrie, Chamberlain, & Clarke, 1988;Reynolds & Eaton, 1986;Stephens, 1987;Tuckman, Youngman, & Kreizman, 1968;Worden & Sterling-Smith, 1973).…”
mentioning
confidence: 99%